STUDIES ON ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF SALMONELLA ISOLATES FROM CHENNAI, INDIA - GOPAL MUTHU,; ARUMUGAM SURESH,; GNADESIKAN SUMATHY,; RAMESH SRIVANI, (International Journal of Pharma and Bio Sciences, 2011)
Typhoid fever is a major health problem as the causative agent Salmonella enterica serovar typhi and paratyphi A has developed resistance to many antimicrobial agents. The study was undertaken to find out the antimicrobial susceptibility pattern of Salmonella isolates. We have studied 176 Salmonella isolates - 172 blood isolates, 3 stools isolates and one isolate from bone marrow. Antimicrobial susceptibility testing was done by disc diffusion method and MIC by agar dilution method. Out of 176 Salmonella isolates, 133 were S. typhi, 41 were S.paratyphi A and 2 were S.typhimurium. 98.5% of S.typhi and 92.7% of S.paratyphi A were resistant to nalidixic acid by MIC studies. 95.5% S.typhi and 97.6% of S.paratyphi A were found to have reduced susceptibility (0.125-0.5µg/ml) by MIC studies as reported earlier. As per CLSI standard MIC value of ≤ 1µg/ml is taken as sensitive, ≥ 4µg/ml is taken as resistance for Salmonella isolates.